Pengaruh Kinerja Keuangan Terhadap Harga Saham Perbankan Di Bursa Efek Indonesia - Qomariah Lahamid; Hendra Gunawan; Desrir Miftah (Jurusan Akuntansi Politeknik Negeri Padang, 2023)
This study aims to determine and analyze the effect of Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Net Profit Margin (NPM), Net Interest Margin (NIM) and Loan To Deposit Ratio (LDR) on stock prices in the state-owned bank group. as well as the National Private Bank groups listed on the Indonesia Stock Exchange for the period 2017 – 2021 and find out the differences. The research method used is descriptive quantitative method and census sampling technique. The results of the study concluded that partially CAR, NPM and NIM had a significant effect on stock prices in the state-owned bank group and in the national private bank group. NPL and LDR partially have a significant negative effect on stock prices in the state-owned bank group and in the private bank group. Statistically, there is no difference in the effect of CAR, NPL, NPM, NIM, and LDR on share prices in the state-owned bank group and in the national private bank group listed on the Indonesia Stock Exchange.